Effects Of Strontium And Samarium Dopants On The Dielectric Properties Of Nickel Oxide - Mohd Salim, Nurul Nadia (2017)
Nickel oxide (NiO) has attracted many researchers to explore its uses in apllications such as electrochoramic films, catalyst, gas sensor, diode and others. This is due to its high properties in chemical, electrical and optical stabilities. In this research, the effect of strontium ions (Sr2+) and samarium ions (Sm3+) dopants on dielectric properties of NiO was investigated. The dielectric properties studied in this research are dielectric constant, εr and dielectric loss, tan δ. The electroceramic system of Ni(1-x)SrxO, Ni(1-x)SmxO where x = 0.01 to 0.10 mol.% and SrxSmyNi(1-x-y)O, where x = 0.03, y = 0.01 to 0.10 mol.% were prepared through solid state reaction method. The samples were sintered at 1200 °C (3 hours soaking time), respectively. Ni(1-x)SrxO was sintered at 1100 to 1300 ºC (1, 3, 6 and 10 hours soaking time). Sample that sintered at 1200 ºC for 3 hours soaking time was identified as optimum sintering parameters. X-Ray diffraction (XRD) analysis on sintered sample showed the phase formation of Ni(1-x)SrxO, Ni(1-x)SmxO and Ni(1-x-y)SrxSmyO. Field Emission Scanning Electron Microscopy (FESEM) observation on the Ni(1-x)SrxO shows the grain size becoming larger with the increasing sintering temperature. The FESEM was repeated with Ni(1-x)SmxO and Ni(1-x-y)SrxSmyO. The three systems showed their grain size was increasing with increasing amount of dopants. The densification of Ni(1-x)SrxO, Ni(1-x)SmxO and Ni(1-x-y)SrxSmyO was improved using Sr2+ and Sm3+ doping and the porosity decrease at higher dopant concentration (x, y). The dielectric behaviour is measured in a wide frequency range of 1 to 1000 MHz. The increase of εr is associated with the decrease of tan δ. The optimum composition for Ni(1-x)SrxO and Ni(1-x)SmxO was obtained for x equals to 0.03 and 0.05 mol.% sample with highest εr (3.24 x 103 and 4.85 x 103) and lowest tan δ (1.42 and 0.19) at 1 MHz. The optimum composition for Ni(1-x-y)SrxSmyO, was obtained at y = 0.03 mol.% sample with highest εr (5.41 x 103) and lowest tan δ (0.13) at 1 MHz.